2007
DOI: 10.1097/01.aog.0000278078.45640.13
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive Efficacy of a Novel Spermicidal Microbicide Used With a Diaphragm

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Mild genital irritation and moderate colposcopic findings were slightly more frequent in the BufferGel and Acidform groups compared with KY Jelly [48]. A contraceptive effectiveness trial of BufferGel with diaphragm demonstrated no significant difference in colposcopic findings or genital symptoms compared with the control arm [13]. The control for this study was the diaphragm used with nonoxynol-9 (N-9), which causes genital epithelial disruption with frequent use [49].…”
Section: Vaginal Defense Enhancersmentioning
confidence: 84%
See 1 more Smart Citation
“…Mild genital irritation and moderate colposcopic findings were slightly more frequent in the BufferGel and Acidform groups compared with KY Jelly [48]. A contraceptive effectiveness trial of BufferGel with diaphragm demonstrated no significant difference in colposcopic findings or genital symptoms compared with the control arm [13]. The control for this study was the diaphragm used with nonoxynol-9 (N-9), which causes genital epithelial disruption with frequent use [49].…”
Section: Vaginal Defense Enhancersmentioning
confidence: 84%
“…No agent has, so far, been demonstrated to be effective as a microbicide. It is estimated that approximately 60-80 different products are currently in development including several undergoing safety and effectiveness trials (Table 1) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Several published reviews provide excellent overviews of microbicide clinical research and the development pathway of candidate products [21 ,22 ,23-26,27 ].…”
Section: Introductionmentioning
confidence: 99%
“…BufferGel was tested in conjunction with a diaphragm. Pregnancy rates over a 6-month period were 10.1% compared with the control group using diaphragm with nonoxynol-9 at 12.3% [137]. Unfortunately, neither C31G nor BufferGel has demonstrated significant protection against HIV infection to date [138].…”
Section: Future Spermicidal Agentsmentioning
confidence: 98%
“…The contraceptive effects, safety, and acceptability of this compound have been evaluated in a multicentre, randomised, double-masked, noninferiority trial carried out in 11 centres 35 . In this trial, 621 women who used an acid buffering gel plus diaphragm were compared with 300 women who used a N-9 spermicide plus diaphragm during six months.…”
Section: Searching For New Compoundsmentioning
confidence: 99%